2021
DOI: 10.1079/hai.2021.0005
|View full text |Cite
|
Sign up to set email alerts
|

Best in Show: Public Perceptions of Different Dog Breeds as Service Dogs

Abstract: Recent research has shed light on the amount of discrimination faced by those who require service dogs ( Mills, 2017 ). While most of the research thus far on discrimination against those who use service dogs has pertained to the appearance of the disabled individual, very little has assessed the appearance of the dog in the amount of discrimination an individual faces. The current study aimed to examine the ways in which the breed of dog impacts the way they are viewed as Service Anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…One reason for this is that the media routinely uses the terms interchangeably (e.g., therapy dog and Service Dog) and tends to report on extreme or negative confrontations between the public and working animals. Consequently, public perception studies have become more prevalent in recent years in the American and Australian settings [1,[6][7][8]. There is a dearth of such studies conducted in Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for this is that the media routinely uses the terms interchangeably (e.g., therapy dog and Service Dog) and tends to report on extreme or negative confrontations between the public and working animals. Consequently, public perception studies have become more prevalent in recent years in the American and Australian settings [1,[6][7][8]. There is a dearth of such studies conducted in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the mostly positive reflections on SDs, research has also found that individuals with SDs can experience discrimination based on their disability given that many otherwise "invisible" illnesses (e.g., mental health concerns) become visible through the presence of an SD [8,[10][11][12]. Up to 50% of individuals with an SD report experiencing some form of discrimination when in public, but those with invisible disabilities report experiencing even higher rates of discriminatory experiences [10,12].…”
Section: Introductionmentioning
confidence: 99%